Comparing DXA and air-displacement-plethysmography to assess body composition of male collegiate hockey players - Delisle-Houde, P.; Reid, R. E. R.; Insogna, J. A.; Prokop, N. W.; Buchan, T. A.; Fontaine, S. L.; Andersen, R. E. (The Journal of Strength and Conditioning Research, 2019)
Accurate assessment of body composition is an important consideration for athletes because it is a health/performance variable. However, little is known about the variability in values obtained across different assessment methods for specific athlete populations. The purpose of this study was to compare 2 common laboratory methods that assess body composition: air displacement plethysmography (BOD POD) and dual energy x-ray absorptiometry (DXA). Twenty-nine male collegiate hockey players, (Age = 24.07 ± 1.49, BMI = 26.5 ± 2.74) participated in this study. All participants underwent back-to-back BOD POD and DXA evaluations. Paired t-tests and Bland-Altman analyses were performed to compare differences in fat mass, fat percentage, and fat-free mass between methods. Average fat percentage reported by the DXA and BOD POD was 15.34 ± 3.53 and 11.66 ± 4.82 respectively, resulting in a bias score of 3.78 ± 2.33 kg (t(28) = 8.71, p = 0.001). Average fat mass reported by the DXA and BOD POD was 13.42 ± 3.59 and 10.15 ± 4.54 kg respectively, resulting in a bias score of 3.27 ± 1.92 kg (t(28) = 9.18, p = 0.001). Average fat-free mass reported by the DXA and BOD POD was 73.31 ± 5.30 and 76.25 ± 5.74 kg respectively, resulting in a bias score of -2.93 ± 2.06 kg (t(28) = -7.66, p = 0.001). Our findings can help make more insightful comparisons between studies that use different body composition methodologies among athletic populations.